Improving the Efficiency of an Eddy Current Sensor Measuring the Thickness of a Heat-Resistant Metal Film of Turbine Blades During Its Deposition in Vacuum - В. Хуей; Н. Бен; C. C. Рижков; A. М. Топалов; О. С. Герасін; Ю. О. Вижол (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2022)
The article analyzes the design features and general modeling of an eddy current sensor for measuring thickness of a metal film. The main tasks of the work are formulated to improve the accuracy and efficiency of the eddy current sensor based on the analysis of different solutions in the turbine industry. The purpose of the research is to study the peculiarities of the sensitive element (coil) of the eddy current sensor measuring the thickness of the heat-resistant metal film of the turbine blades in a vacuum chamber, followed by computer simulation of its functioning to identify the optimal parameters of the oscillatory circuit. The set goal is achieved by solving the following problems. Firstly, a constructive implementation of the eddy current sensor of the measuring transducer for working in a vacuum chamber at a temperature of 300°C is proposed. Secondly, the calculation of the sensitive element of the sensor (inductance coil) is performed for operation at elevated temperatures. Thirdly, corrections for the intrinsic and mutual inductance of the turns, as well as the inductance correction from temperature are studied in detail and taken into account when calculating the inductance. Finally, computer simulation of the developed measuring transducer is performed based on the oscillatory circuit and the quality factor conception of the simulation models. The most significant important results of the work are the following: a) the proposed methodology makes it possible to develop an optimal sensitive element for operation in vacuum and at elevated temperatures, and b) the simulation model helps to determine the best electrical parameters of the measuring transducer elements. The significance of the obtained results lies in the possibility of improving the accuracy and, accordingly, the efficiency of measuring the thickness of the heat-resistant metal film of the turbine blades.